A womanist exposition of pseudo-spirituality and the cry of an oppressed African woman - Kobo, Fundiswa Amanda (HTS teologiese studies, 2018)
Women have for centuries suffered different forms of oppression and arguably continue to suffer in subtle forms in the 21st century. Marion Young points to five types of oppression, namely, violence, exploitation, marginalisation, powerlessness and cultural imperialism. For South African black women, all of these types of oppression have manifested three times more as they have suffered triple oppression of race, class and gender to employ the widely used notion of triple jeopardy in the womanist discourses and Black Theology of Liberation. The struggle of women to challenge the patriarchal culture of subordination is still pertinent for our context today. Patriarchy is a reality that has been inscribed in the minds, souls and bodies of these women. It arguably continues to be inscribed in subtle forms. Patriarchy and the oppression of women have been justified and perpetuated by a complex interplay of Christian teachings and practices fused with culture and the use of the Bible. Yet, for these women, church and the Bible continue to be central in their lives. This article looks at the cries of African women in juxtaposition to their prayers, faith and thus spirituality, and to argue that theirs is a pseudo-spirituality. This article is thus a womanist exposition of the pseudo-spirituality of an African woman in a quest for liberation of her spirituality.